2010
DOI: 10.1007/s00382-010-0746-x
|View full text |Cite
|
Sign up to set email alerts
|

Climate–soil–vegetation control on groundwater table dynamics and its feedbacks in a climate model

Abstract: Among the three dynamically linked branches of the water cycle, including atmospheric, surface, and subsurface water, groundwater is the largest reservoir and an active component of the hydrologic system. Because of the inherent slow response time, groundwater may be particularly relevant for long time-scale processes such as multi-years or decadal droughts. This study uses regional climate simulations with and without surface watergroundwater interactions for the conterminous US to assess the influence of cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 50 publications
5
69
0
Order By: Relevance
“…Recent research has shown that a model atmosphere would respond to groundwater dynamics (Anyah et al 2008;Jiang et al 2009;Leung et al 2011). Using a different forcing, CRUNCEP in VARCRU, also has an effect on the variable soil thickness simulation as seen by the drier uppermost soil moisture in the southwestern United States and the northern Great Plains in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that a model atmosphere would respond to groundwater dynamics (Anyah et al 2008;Jiang et al 2009;Leung et al 2011). Using a different forcing, CRUNCEP in VARCRU, also has an effect on the variable soil thickness simulation as seen by the drier uppermost soil moisture in the southwestern United States and the northern Great Plains in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This may not be the case if coupled to an atmospheric model because of potential feedbacks between LH flux and precipitation. Several studies (Anyah et al 2008;Jiang et al 2009;Leung et al 2011) have shown changes to LH flux in response to changes in precipitation caused by the inclusion of groundwater models. At Karakoram and southeastern Africa, LH flux in DEEP is almost the same as in CLM4.5, whereas LH flux in VAR is as much as about 12 W m 22 lower than in DEEP and CLM4.5 (Figs.…”
Section: A Changes To the Mean And Interannual Variabilitymentioning
confidence: 99%
“…Similar approaches are used in the Total Runoff Integrating Pathways (TRIP) model Decharme et al, 2010;Decharme et al, 2012]. However, VIC-GW [Liang et al, 2003;Leung et al, 2011] allows for two-way soil-water table interactions in the vertical direction. 3.…”
Section: A3 Groundwater Dynamicsmentioning
confidence: 99%
“…al., 2015), cloud formation (Rahman et al, 2015), and climate (Leung et al, 2011;Taylor et al, 2013). Lateral subsurface processes are fundamentally important on multiple spatial scales, including hill-slope scales (McNamara et al, 2005;Zhang et al, 2011), basin scales in semiarid and arid climates where regional aquifers sustain baseflows in rivers (Schaller and Fan, 2009) and wetlands (Fan and MiguezMacho, 2011).…”
mentioning
confidence: 99%